Nursing Leadership—Mapping the Challenges of Newly Qualified Nurses in Hospital Units: A Scoping Review Protocol - da Silveira Assoni, Maria Aurélia; do Nascimento Braga, Ana Lucia; da Cunha, Viviane Nunes Tosta; Francisco, Jaquelini Brito; Hisatomi, Guilherme Grici; Martinez, William Donegá; dos Santos, Emerson Roberto; de Souza Menezes, João Daniel; da Silva, Matheus Querino; Quitério, Alex Bertolazzo; de Sales Floriano, Janaína Aparecida; Franco, Rauer Ferreira; et al. (MDPI, 2025)
Background/Objectives: Leadership in nursing plays a pivotal role in the provision of high-quality healthcare. It is, therefore, of paramount importance to understand the challenges encountered by newly qualified nurses when assuming leadership responsibilities. This scoping review protocol aims to identify and map these challenges, thereby facilitating the development of more effective interventions and support programmes. The data collection and analysis were conducted from January 2024 to March 2024. Methods: The review was conducted in accordance with the Joanna Briggs Institute (JBI) guidelines for scoping reviews and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) recommendations. A comprehensive search was undertaken across MEDLINE, CINAHL, Web of Science, Scopus, LILACS, and SciELO databases, in addition to a search for the grey literature. Study selection was performed by two independent reviewers, applying pre-defined inclusion and exclusion criteria. The data were extracted using a standardised form and analysed descriptively. Results: The review identified several key challenges faced by newly qualified nurses in leadership roles, including conflict management, decision-making under pressure, and effective communication. These findings highlight the complexity of transitioning from academic training to professional practice. The results provide a comprehensive overview of these challenges, enabling the identification of gaps in the existing knowledge base and informing the direction of future research and interventions. Conclusions: The findings of this review will contribute to the enhancement of healthcare quality and the promotion of the professional development of newly qualified nurses. This research underscores the importance of developing targeted interventions and support systems to address the specific challenges identified, thereby influencing nursing practice and policy.